Konstruksi Identitas Fanboy K-Pop dalam Relasi Sosial dan Pemaknaan Komunal - Maulidina Maulidina; Yoka Pradana (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Male K-pop fans (fanboys), amid the dominance of female fans within K-pop fandom, frequently encounter negative stigmatization because their participation is often perceived as inconsistent with societal norms of masculinity. Such conditions influence how fanboys construct and negotiate their identities. This study investigates the identity construction of K-pop fanboys through the lens of the Communication Theory of Identity (CTI). Using a qualitative case study approach, data were collected through in-depth interviews with nine informants selected through purposive sampling and non-participant observation of fandom-related activities and social media engagement. The findings show that fanboy identity is constructed through the interaction of the personal, enactment, relational, and communal layers of identity. At the personal layer, informants identified themselves as either casual or devoted fans. These identities were expressed through fandom activities, ownership of K-pop merchandise, and social media engagement. At the relational layer, older sisters and female friends played important roles in introducing and reinforcing involvement in K-pop culture. At the communal layer, fanboys were frequently labeled as banci and/or insufficiently masculine, leading them to either conceal or openly express their fandom identity. This study concludes that K-pop fanboy identity is dynamic and continuously negotiated within societal expectations of masculinity.